PENGELOLAAN ARSIP DOKUMEN KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PARIAMAN - Marlinda, Marlinda (JESS (Journal of Education on Social Science); Vol 4 No 2 (2020): Social and Educational Issues in Public ServiceDO - 10.24036/jess.v4i2.286, 2020)
Archives needed to be managed properly because archives have a very important role for the life of an institution/organization so that if there were someone who needed them, the archives could be provided quickly and accurately. The objectives of this research were to analyze the management of population document archives at the Department of Population and Civil Registration of Pariaman City in connection with the creation, arrangement, storage, and discovery of archives; to analyze the obstacles in managing the population document archives; and to formulate the solutions (efforts) that could be done in overcoming problems or obstacles encountered by the archive manager. This was a qualitative research. The finding of this study indicated that the current management of population document archives at Pariaman City was not optimal and has not been implemented properly so that the management system needed to be improved. It was necessary to establish a Standard Operating Procedure (SOP) in the field of archiving so that activities for archiving could be well controlled .